2017
DOI: 10.1097/qad.0000000000001499
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HIV infection is an important health determinant in non-HIV-infected infants

Abstract: Objective: To assess morbidity and mortality in HIV-exposed uninfected (HEU) children to help guiding appropriate clinical care and effective preventive interventions.Design: This is a longitudinal study comparing two cohorts of children; one born to HIV-infected women and the other born to HIV-uninfected women. Methods:We have analyzed prospectively obtained information on nutritional status, morbidity and mortality from 966 HEU and 909 HIV-unexposed infants followed up until their first 18 months of life at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
7
26
1
Order By: Relevance
“…The present findings both accord with and contradict previous studies from sub-Saharan Africa reporting on increased risk of developmental delays and poor nutritional status among HEU as compared to HUU children [20][21][22]. Notably, studies indicate that before the universal availability of antiretroviral therapy, ART, HEU children had higher mortality-, morbidity and growth failure risk than HUU children, whereas later studies from the ART era show heterogeneous findings [22]. In a meta-analytic review of neurodevelopment in young children born to mothers with HIV, Mc Henry et al [40] found that children with HIV-1 and HEU had worse health outcomes than their HUU counterparts and moreover, that HEU children without exposure to ART had worse health outcomes than their ART exposed counterparts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present findings both accord with and contradict previous studies from sub-Saharan Africa reporting on increased risk of developmental delays and poor nutritional status among HEU as compared to HUU children [20][21][22]. Notably, studies indicate that before the universal availability of antiretroviral therapy, ART, HEU children had higher mortality-, morbidity and growth failure risk than HUU children, whereas later studies from the ART era show heterogeneous findings [22]. In a meta-analytic review of neurodevelopment in young children born to mothers with HIV, Mc Henry et al [40] found that children with HIV-1 and HEU had worse health outcomes than their HUU counterparts and moreover, that HEU children without exposure to ART had worse health outcomes than their ART exposed counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…On the other side there were indications of a minor developmental delay in eruption of permanent teeth among HEU children presenting with significantly higher number of non-exfoliated primary teeth than HUU children [45]. The present findings both accord with and contradict previous studies from sub-Saharan Africa reporting on increased risk of developmental delays and poor nutritional status among HEU as compared to HUU children [20][21][22]. Notably, studies indicate that before the universal availability of antiretroviral therapy, ART, HEU children had higher mortality-, morbidity and growth failure risk than HUU children, whereas later studies from the ART era show heterogeneous findings [22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although the effects of exposure to HIV‐1 during pregnancy, delivery, and lactation on the postnatal development of HEU children remain uncertain, previous studies in sub‐Saharan Africa have reported increased infant morbidity according to low maternal CD4 counts, which is not explained by maternal mortality . By contrast, low maternal CD4 count did not increase the IRRs of having caries in primary teeth for the HEU children investigated in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…On the other side there were indications of a minor developmental delay in eruption of permanent teeth among HEU children presenting with significantly higher number of nonexfoliated primary teeth than HUU children [45]. The present findings both accord with and contradict previous studies from sub-Saharan Africa reporting on increased risk of developmental delays and poor nutritional status among HEU as compared to HUU children [20][21][22]. Notably, studies indicate that before the universal availability of antiretroviral therapy, ART, HEU children had higher mortality-, morbidity and growth failure risk than HUU children, whereas later studies from the ART era show heterogeneous findings [22].…”
Section: Discussionsupporting
confidence: 83%